Doing interpretive research in a technocratic age: A clash of paradigms - Donna M. Chovanec (Adult Education Research Conference, 1996)
This paper uses Habermas’ paradigmatic conception to look critically at a research experience. It is postulated that a clash between an interpretive research approach and an institutional technocratic positivism was revealed through competing interests. Following a review of the paradigms and the research situation, conflicts around value, control and simplicity are discussed.